Ersonified diagnostic and correction dyslipidemia approach by profiling of apolipoproteins - M. A. Kachkovsky; I. P. Vvedenskaya; V. Yu. Vvedensky; A. A. Supilnikov; J. V. Ponomareva; M. N. Milyakova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
Many questions remain in the diagnosis, treatment, and prevention of dyslipidemia, despite the available clinical recommendations. Among these issues is the cause of cardiovascular diseases, when achieving and maintaining the target values of lipid metabolism. We need to change the existing paradigm. Apolipoproteins as protein components of lipoproteins can significantly more accurately characterize the dyslipidemic status of a patient, since their structure and composition are unique. A personalized strategy for the prevention and treatment of dyslipidemia is possible based on the apolipoprotein profile. At present, new data on the functions of apolipoproteins, their genetic polymorphisms, and molecular preparations for correcting their content and lipid metabolism have been proposed.